Pengaruh Promosi dan Lokasi Terhadap Keputusan Pembelian Pada Kedai Mie Korea - Hartini, Sri; Sari, Dewi Ratna (Universitas Nusa Putra, 2020)
Promotion is an important activity to communicate or inform the superiority of the product and persuade prospective customers to purchase the product offered. Location is a decision in which a company makes its business by operating and its staff is placed in a location factor that is right and right so that consumers also have their decision in choosing or buying which will affect the success of a business. The purchasing decision is a stage where consumers have alternative or more choices in deciding whether or not to buy an item or service. This study aims to analyze the effect of promotion and location on purchasing decisions at Kedai Mie Korea. This research is quantitative. The population of this study is consumers who visited the Kedai Mie Korea. Data were collected by distributing questionnaires to 100 respondents using a non-probability sampling technique. The method used is descriptive and verification methods. The type of data used in this study is primary data obtained from the distribution of questionnaires and secondary data obtained from sales data. Data is processed using simple linear regression analysis. The results of this study prove that Promotion and Location have a positive and significant effect on Purchasing Decisions.